2022
DOI: 10.1099/ijsem.0.005284
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic and comparative genomic analyses of Leuconostocaceae species: identification of molecular signatures specific for the genera Leuconostoc, Fructobacillus and Oenococcus and proposal for a novel genus Periweissella gen. nov.

Abstract: The genera Convivina , Fructobacillus , Leuconostoc , Oenococcus and Weissella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 65 publications
(151 reference statements)
0
31
0
Order By: Relevance
“…The genomes were inspected for completeness and contamination with CheckM (Parks et al, 2015 ). Genomes were also checked for the presence of the molecular signatures characterizing the genus Leuconostoc (Bello et al, 2022 ). The genomes were annotated with Prokka (Seemann, 2014 ) to calculate the pangenome using Roary (Page et al, 2015 ), with the minimum percentage identity parameter set at 80%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genomes were inspected for completeness and contamination with CheckM (Parks et al, 2015 ). Genomes were also checked for the presence of the molecular signatures characterizing the genus Leuconostoc (Bello et al, 2022 ). The genomes were annotated with Prokka (Seemann, 2014 ) to calculate the pangenome using Roary (Page et al, 2015 ), with the minimum percentage identity parameter set at 80%.…”
Section: Methodsmentioning
confidence: 99%
“…The present project aims to investigate the evolutionary relationships within the genus Leuconostoc through a phylogenomic approach and to verify the consistency of phylogenetic relationships with the current taxonomy. This genus holds a group of Lactic Acid Bacteria (LAB) belonging, together with the genera Convivina, Fructobacillus, Oenococcus, and Weissella, to the family of Leuconostocaceae (www.bacterio.net; Nieminen et al, 2014;Bello et al, 2022), in its turn included in the order Lactobacillales, based on the average amino acid identity of core proteins (cAAI) (Zheng et al, 2020). The genus Leuconostoc encompasses 17 species according to the List of Prokaryotic names with Standing in Nomenclature (https://lpsn.dsmz.de/genus/leuconostoc) (Parte et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This genus has undergone several reclassifications. While some species that were originally classified under the genus Leuconostoc were reclassified as Oenococcus, Fructobacillus, and Weissella, others have been considered heterotypic synonyms (Björkroth et al, 2014;Bello et al, 2022). Most recently, the previously reported Leu.…”
Section: Introductionmentioning
confidence: 99%
“…Whole-genome sequencing is widely used to determine the taxonomic position of microorganisms (Kumar et al, 2022). Recent comparative genomic studies have confirmed that the average nucleotide identity (ANI) and digital DNA-DNA hybridization (dDDH) might suffice to classify Leuconostoc species at the species or subspecies level (Wu and Gu, 2021;Bello et al, 2022). Also, more robust approaches (e.g., pan-and core-genome analysis) were used to account for strain diversity and classify closely related species or subspecies (Kim et al, 2021(Kim et al, , 2022b.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent iteration of FoodMicrobionet uses SILVA v138.1 as a taxonomic reference database (https://www.arb-silva.de/documentation/release-1381/ last accessed in July 2022). This allows the taxonomic assignment of Amplicon Sequence Variants (ASV) to the genera proposed by Zheng et al (2020) but does not allow the taxonomic assignment for the new genera Convivina and Periweissella (Bello et al, 2022; Praet et al, 2015). FoodMicrobionet includes studies which have used a large variety of target regions within the 16S gene, although those using V1-V3, V3-V4 and V4 represent the vast majority.…”
Section: Introductionmentioning
confidence: 99%